Penerapan Manajemen Bencana Di Desa Cibenda Kecamatan Parigi Kabupaten Pangandaran, Sebagai Kampung Siaga Bencana Dalam Mengantisipasi Potensi Bencana - Asep Setiawan; Yanyan Agustian; Bambang Eko Widyanto (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
Disaster management is a series of activities carried out in the context of prevention, mitigation, preparedness, emergency response and recovery efforts related to disasters. Disaster management is carried out with the aim of reducing losses and risks that may occur and speeding up the post-disaster recovery process. The implementation of disaster management is very necessary for the people of Cibenda Village because the village is located in a disaster-prone area. The target of this activity is the people of Cibenda Village and its surroundings. The methods used are interactive lectures, discussions and simulations as appropriate methods to provide understanding to the public. Meanwhile, location surveys are carried out to find out evacuation routes that can be used by the community when a disaster occurs. The output of this community service activity is a module for socializing the application of disaster management, scientific articles, as well as planning evacuation routes and handing over disaster evacuation tools.